GAMBARAN KEJADIAN VENTILATOR-ASSOCIATED PNEUMONIA PADA PASIEN YANG DIRAWAT DI ICU DAN CVCU RSUD ARIFIN ACHMAD PERIODE JANUARI 2013 s/d AGUSTUS 2014 - Nency, Cahyu; Andrini, Fauzia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTPneumonia classification into two groups. There are community acquiredpneumonia and nosocomial pneumonia. Ventilator-associated pneumonia (VAP) isdefined as nosocomial pneumonia that occurred in patient after 48 hours usedendotracheal tube. It is a common condition, difficult to diagnose accurately, andexpensive to treat.VAP incidence consequence the length of stay and increasemorbidity and mortality patient in ICU. This descriptive retrospective study explainedthe overview incidence VAP of patient in ICU and CVCU RSUD Arifin AchmadGeneral Hospital of Riau Province Januari 2013 until August 2014 period. The datacollect from medical record of patients in ICU and CVCU. In this study, 113 patientswere used mechanical ventilation more than 48 hours. The prevalence of VAP in thisstudy was 18,58%(21 patients). By the sex, the most common of patients with VAPwas female consist of 12 patients (57,2%) . By the age group, the most common ofpatients with VAP was < 60 years consist of 16 patients (76,2%). By the onset ofVAP, the most common of patients was early onset consist of 20 patients (45,2%).Keywords:Ventilator-associated pneumonia, mechanical ventilation, incidenceoverview